Seismic Performance Evaluation of an Eight-Story Reinforced Concrete Apartment Building with Special Moment-Resisting Frame in Kubu Raya Regency - Santana, Fagan Resha; Budi, Gatot Setya; Yusuf, M. (Jurnal Teknik Sipil, 2026)
This study presents the structural analysis and seismic performance evaluation of an eight-story reinforced concrete apartment building in Kubu Raya Regency, Indonesia, designed using a Special Moment Resisting Frame (SMRF) system. The design follows the seismic and detailing requirements of SNI 1726:2019 and SNI 2847:2019. A three-dimensional finite element model was developed in ETABS, with beams and columns modeled as frame elements and slabs as shell elements, incorporating stiffness-reduction factors to represent cracked-section behavior. Structural analysis considered gravity, wind, and seismic loads in accordance with SNI 1727:2020 and SNI 1726:2019. Seismic performance was evaluated using response spectrum analysis, ensuring at least 90% modal mass participation in each principal direction. Performance checks included inter-story drift limits, earthquake force scaling, P-Delta effects, and horizontal and vertical irregularities. The results show that all seismic performance criteria are satisfied, with inter-story drifts within allowable limits and stable structural behavior. Reinforcement detailing for all structural components complies with SMRF requirements, ensuring adequate ductility. The foundation system using driven piles was verified based on site-specific SPT data. Overall, the structural system demonstrates sufficient strength, stiffness, and seismic reliability.